Genetic diversity and population structure analysis in wild strawberry (Fragaria nubicola L.) from Motuo in Tibet Plateau based on simple sequence repeats (SSRs). (December 2015) - Meng, Fanjuan; Liu, Li; Peng, Mu; Wang, ZhongKui; Wang, Chao; Zhao, Yiyong
Abstract: Germplasms resources of wild strawberry are rich in Motuo country of Tibet, China. In this study, we assessed genetic diversity of seventy wild strawberry germplasms from different geographical regions using simple sequence repeat (SSR) markers. The genetic diversity of wild strawberry was demonstrated by 189 polymorphic SSR-PCR bands obtained using ten selective primers. Additionally, the average polymorphic information content ( PIC ), total gene diversity and population diversity were 0.941, 0.331 and 0.214, respectively. At the population level, variation of strawberry accessions among population was higher than that within population. Based on arithmetic mean (UPGMA) dendrogram method, all samples were clustered into 6 groups and two subgroups. Combined with the results of UPGMA and Principle coordinate analysis, wild strawberry accessions tended to group by geographic origin. Thus, these findings will benefit for the protection and exploitation of wild strawberry, and provide theoretical basis for further study in the origin and phylogenetic systematics of wild strawberry. Highlights: We firstly used SSR method to analyze genetic diversity of wild strawberry resources from MT. Wild strawberry has a broad genetic background. Wild strawberry from MT should receive special attention to ensure their conservation.